The Role Of Service Quality In Mobile Government: Effects On Customer Satisfaction, Loyalty And Reuse Intention - Siluveru Suresh, Dr. Rasheed K. (European Economic Letters (EEL), 2025)
The study examines the impact of service quality on client satisfaction, loyalty, and intention to reuse in mobile government (m-Government) services. The increasing dependence on digital governance necessitates the provision of effortless, efficient, and dependable services to maintain user engagement. The study utilizes a quantitative analytic technique, examining data from a sample of 384 respondents and applying AMOS for statistical evaluation. Essential techniques, such factor loadings and reliability testing, evaluate the interconnections of service quality, customer satisfaction, and loyalty. The results indicate that service quality substantially improves customer satisfaction, resulting in heightened confidence and engagement with m- Government platforms. Furthermore, customer happiness significantly impacts loyalty, underscoring the need of user-friendly and secure services. Moreover, service quality independently influences loyalty, suggesting that customers maintain commitment when services are effective and dependable. Customer satisfaction mediates the relationship between service quality and loyalty, underscoring the necessity for ongoing service enhancements. The research underscores the necessity of maintaining elevated service standards, accessibility, and security to promote sustained acceptance and confidence in digital government, offering critical insights for policymakers and service providers to improve m-Government platforms. Keywords: Mobile Government (m-Government), Service Quality, Customer Satisfaction, Customer Loyalty (Reuse Intention).